Attentional differences in a driving hazard perception task in adults with autism spectrum disorders - Sheppard, Elizabeth; van Loon, Editha; Underwood, Geoffrey; Ropar, Danielle (Springer, 2016)
The current study explored attentional processing of social and non social stimuli in ASD within the context of a driving hazard perception task. Participants watched videos of road scenes and detected hazards while their eye movements were recorded. Although individuals with ASD demonstrated relatively good detection of driving hazards, they were slower to orient to hazards. Greater attentional capture in the time preceding the hazards’ onset was associated with lower verbal IQ. The findings suggest that individuals with ASD may distribute and direct their attention diferently when identifying driving hazards.